PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA KOPERASI UNIT DESA (KUD) SEJAHTERA BABAT TOMAN - Novita Sari; Fadilla Fadilla; Havis Aravik (FEB Universitas Maritim Semarang, 2022)
This study aims to analyze the effect of motivation and work discipline on employee performance at KUD Sejahtera Babat Toman. Samples were selected using the saturated sample technique. Data for 40 respondents was collected through a questionnaire. This research implements multiple linear regression method to analyze the data. The data collection technique in this study used a questionnaire technique. The data analysis technique in this study uses the Classical Assumption Test, Multiple Regression, Hypothesis Testing (t-test and F-test), and the coefficient of determination. The data processing in this study used the SPSS (Statistical Package for the Social Science) software program version 23.00. The results of the investigation show that partially motivation has a significant and positive effect on the performance of KUD Sejahtera Babat Toman employees with a t count > t table or (3.372 > 2.028). or (0.806 < 2.028). However, simultaneously motivation and work discipline have a significant effect on employee performance with the value of F arithmetic > F table or (11.371> 3.25). This fact is useful for KUD Sejahtera Babat Toman to improve employee performance, so the company must consider motivation and work discipline factors together.